Correlation between stunting children aged 6-7 years in term of nutritional status and the eruption of permanent first molar - Fadilla, Nadia Dwi; Wardani, Riana; Putri, Fidya Meditia (Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: Stunting is one of the nutritional problems that occur in Indonesia. Stunting is a condition where height is not following age. Physical growth is often used as an indicator to measure nutritional status. Permanent first molars are the first to erupt and normally erupt at 6-7 years old. Nutrition plays an important role in the growth and development of children. Since nutrition is one of the factors that influence tooth eruption, this study aimed to analyse the correlation between stunting children aged 6-7 years in terms of nutritional status and the eruption of the permanent first molar. Methods: This research used observational analytic correlation with a cross-sectional approach. Sampling was done using the cluster random sampling method to select elementary schools and total sampling to select children. The research was conducted at three elementary schools in the Jatinangor region. The number of samples was 200 children. The samples were measured for height and examination of the eruption status of permanent first molars. Result: It was found that 42 children were stunted. 12 children had not erupted their permanent first molars at all. There were 36% stunted children aged 6 years and 64% children aged 7 years. The results of the analysis using the Spearman rank correlation test obtained a correlation coefficient with r=0.185 and p-value=0.242 which showed the very weak strength and positive direction of the correlation. Conclusion: There is no correlation between nutritional status and eruption of permanent first molars in stunting children aged 6-7 years in the Jatinangor region.Keywords: nutritional status; stunting; tooth eruption; permanent first molar